Forecasting international demand for Philippine tourism - Rufino, Cesar C. (Animo Repository, 2011)
Time series forecasting models for tourist arrivals to the Philippines from the top 12 source countries are empirically developed in this paper. Together with a reliable procedure of modeling background noise, this study employed a modeling framework which took into account influential events that impact on the level and direction of arrival series. From this framework, the study was able to establish twelve time series models for the monthly incoming tourism traffic from the top tourists sending countries to the Philippines for use in predicting future visitor arrivals scenarios. © 2011 De La Salle University, Philippines.